Identification And Evaluation Of Performance Appraisal Uses In The Malaysia France Institute (Mfi) - Tai, Jasmin Siew Ping (1999)
This study tried to identify and evaluate the uses of performance appraisal. 60 out of 65 questionnaire were collected and this account for about 92% of the sample. The findings showed that uses of performance appraisal; salary increment, promotion and individual training needs were ranked as the most important, second most important and third most important by the respondents. In addition, the researcher found that the perception on the most important and second most important use of performance were the same between the academic and non-academic staff. However, the third most important use of performance appraisal for non-academic staff was to provide performance feedback but for the academic staff was to identify individual training needs. Based on the findings, the researcher also found that these two groups of employees have different perception about the uses of performance appraisal except for salary increment and to identify promotion for potential staff. Besides, this study indicated that the employees and organization showed they had the same perception about the three main uses of performance appraisal (salary increment. promotion and training needs). However, there are still some different perceptions about the uses of performance appraisal due to lack of communication between organization and employees. It can be eliminated using communication processes in information technology such as availability of computer system.